2015
DOI: 10.1159/000381804
|View full text |Cite
|
Sign up to set email alerts
|

Kinect-Based Five-Times-Sit-to-Stand Test for Clinical and In-Home Assessment of Fall Risk in Older People

Abstract: Background: Accidental falls remain an important problem in older people. The five-times-sit-to-stand (5STS) test is commonly used as a functional test to assess fall risk. Recent advances in sensor technologies hold great promise for more objective and accurate assessments. Objective: The aims of this study were: (1) to examine the feasibility of a low-cost and portable Kinect-based 5STS test to discriminate between fallers and nonfallers and (2) to investigate whether this test can be used for supervised cli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
89
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(95 citation statements)
references
References 21 publications
5
89
0
1
Order By: Relevance
“…These more subtle changes might allow us to classify those at risk of falling at an earlier stage, and allow us to effectively guide and measure treatment. Indeed, two studies that examined the use of inertial sensors and Kinect sensors during the Five Time Sit to Stand test found that these methods of measuring performance successfully discriminated between fallers and non‐fallers in the older population . The present study also shows that the addition of a dual task to the TUG test results in a deterioration in performance, not only in the overall time to complete the test, but also in specific components of the test, and in certain test and gait parameters, such as walking speed, sit‐to‐stand time, stand‐to‐sit time and time to turn.…”
Section: Discussionsupporting
confidence: 55%
See 1 more Smart Citation
“…These more subtle changes might allow us to classify those at risk of falling at an earlier stage, and allow us to effectively guide and measure treatment. Indeed, two studies that examined the use of inertial sensors and Kinect sensors during the Five Time Sit to Stand test found that these methods of measuring performance successfully discriminated between fallers and non‐fallers in the older population . The present study also shows that the addition of a dual task to the TUG test results in a deterioration in performance, not only in the overall time to complete the test, but also in specific components of the test, and in certain test and gait parameters, such as walking speed, sit‐to‐stand time, stand‐to‐sit time and time to turn.…”
Section: Discussionsupporting
confidence: 55%
“…Indeed, two studies that examined the use of inertial sensors and Kinect sensors during the Five Time Sit to Stand test found that these methods of measuring performance successfully discriminated between fallers and non-fallers in the older population. 31,32 The present study also shows that the addition of a dual task to the TUG test results in a deterioration in performance, not only in the overall time to complete the test, but also in specific components of the test, and in certain test and gait parameters, such as walking speed, sit-tostand time, stand-to-sit time and time to turn. Although there is little research directly comparing the effect of MTand CTon gait, the present study suggests that the nature of the dual task is important in affecting performance, with a CT involving a mental tracking task, disturbing overall performance more than a MT, which might be more automatic in nature and require less competition for resources.…”
Section: Discussionsupporting
confidence: 50%
“…the time in which both feet are in contact with the ground), variability of stride velocity, mean duration and variability of a single walking sequence, and so on; postural balance features, related to the skeleton posture during motion. For evaluating the frailty it is important to consider both of these parameters [5,13,25].…”
Section: Proposed Methodsmentioning
confidence: 99%
“…Yang et al [21] have investigated the reliability of the sensor for evaluating standing balance for postural control. There are many examples of Kinect usage for in-home monitoring of elderly, especially for fall risk assessment: measuring of stride-to-stride gait variability [22]; monitoring of human centroid height relative to the ground and body velocity [23]; testing a two-stage fall detection system [24]; implementing the five-times-sit-to-stand (5STS) test, a functional test to assess fall risk and discriminate between fallers and non-fallers [25].…”
Section: Related Workmentioning
confidence: 99%
“…이와 같은 키넥트 센서를 이용한 선행연구에서 는 균형능력 증진을 위한 기능성 게임 [10,11] 및 재활훈련 [12] 을 적용한 다양한 프로그램들을 개발하였다. 그러나 선행연구의 대부분은 흥미를 유발하기 위한 게임요소에 e점이 맞춰짐에 따 라 [13] [3,4,16].…”
unclassified